2011
DOI: 10.1095/biolreprod.110.088476
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Estrogen Synthesis Alters MIR202* Expression in Embryonic Chicken Gonads1

Abstract: Tissue-specific patterns of microRNA (miRNA) expression contribute to organogenesis during embryonic development. Using the embryonic chicken gonads as a model for vertebrate gonadogenesis, we previously reported that miRNAs are expressed in a sexually dimorphic manner during gonadal sex differentiation. Being male biased, we hypothesised that up-regulation of microRNA 202* (MIR202*) is characteristic of testicular differentiation. To address this hypothesis, we used estrogen modulation to induce gonadal sex r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 46 publications
2
55
0
Order By: Relevance
“…In the chicken embryo, we have shown that miR-202-5p is expressed with a male bias during embryonic gonad development (Bannister et al 2009(Bannister et al , 2011. MiR-202-5p expression is reduced in male and female embryos treated with oestrogen (estradiol-17β) and increased in female embryos treated with oestrogen inhibitors (Bannister et al 2011). This suggests that miR-202-5p may play a role downstream of oestrogen signalling, perhaps in maintaining the testis phenotype.…”
Section: Potential Roles For Mirnas During Embryonic Gonad Developmenmentioning
confidence: 95%
See 3 more Smart Citations
“…In the chicken embryo, we have shown that miR-202-5p is expressed with a male bias during embryonic gonad development (Bannister et al 2009(Bannister et al , 2011. MiR-202-5p expression is reduced in male and female embryos treated with oestrogen (estradiol-17β) and increased in female embryos treated with oestrogen inhibitors (Bannister et al 2011). This suggests that miR-202-5p may play a role downstream of oestrogen signalling, perhaps in maintaining the testis phenotype.…”
Section: Potential Roles For Mirnas During Embryonic Gonad Developmenmentioning
confidence: 95%
“…We have previously shown miR-202-5p to be up-regulated in males from the point of differentiation and that its expression is altered by oestrogen levels (Bannister et al 2011). With this in consideration, miR-202-5p may act to modulate TGF-β signalling in differentiated testis.…”
Section: Potential Roles For Mirnas During Embryonic Gonad Developmenmentioning
confidence: 96%
See 2 more Smart Citations
“…In both species, they are expressed in the key Sertoli cell lineage. In chickens, experimental male-to-female sex reversal with oestrogen causes a decline in chicken miR-202-3p expression (Bannister et al 2011). Interestingly, miR-202-3p also was found to be one of the main miRNAs depleted in the sterile gonads of Xenopus hybrids, suggesting it is important for gametogenesis (Michalak & Malone 2008).…”
Section: Regulation Of Mirna Expression By Sox9 During Mammalian Sertmentioning
confidence: 99%